VIRALITAS DAN AGAMA: DISKURSUS PUBLIK TENTANG THARIQ HALILINTAR DAN FENOMENA HAJI DI USIA DINI - Faisal (PRESIDENSI: Jurnal Politik dan Pemerintahan, 2025)
The phenomenon of awarding the title “Haji” to Thariq Halilintar—who was said to have performed the Hajj pilgrimage at only two months old—sparked widespread controversy in Indonesia’s digital public sphere. This study aims to analyze how the media framed the event, how Islamic jurisprudence views Hajj performed by minors, and how the social meaning of the “Haji” title is constructed and interpreted by society. Using a qualitative descriptive approach and critical discourse analysis, data were collected from online news outlets (DetikHikmah, Suara.com, Kumparan), YouTube content from the Gen Halilintar family, and public comments on social media. Theoretical frameworks include communication theories (framing and agenda setting), Islamic thought (maqasid al-shariah and fiqh of worship), and social theory (symbolic interactionism). The findings reveal that the media framed the issue as a religious entertainment controversy, shaping public perception beyond factual reporting. From an Islamic legal perspective, Hajj performed by a child is valid but does not fulfill the obligation in adulthood, and the “Haji” title is more of a cultural symbol than a formal religious designation. Public responses indicate that the title has become performative, with netizens debating its authenticity and purpose. The study concludes that digital platforms have become a new arena for the contestation of religious symbols, blurring the boundaries between the sacred and the profane in contemporary Muslim society